Pharmacological Modulation and (Patho)Physiological Roles of TRPM4 Channel—Part 1: Modulation of TRPM4 - Zsigmond Máté Kovács; Csaba Dienes; Tamás Hézső; János Almássy; János Magyar; Tamás Bányász; Péter P. Nánási; Balázs Horváth; Norbert Szentandrássy (Pharmaceuticals, 2022)
Transient receptor potential melastatin 4 is a unique member of the TRPM protein family and, similarly to TRPM5, is Ca2+-sensitive and permeable to monovalent but not divalent cations. It is widely expressed in many organs and is involved in several functions by regulating the membrane potential and Ca2+ homeostasis in both excitable and non-excitable cells. This part of the review discusses the pharmacological modulation of TRPM4 by listing, comparing, and describing both endogenous and exogenous activators and inhibitors of the ion channel. Moreover, other strategies used to study TRPM4 functions are listed and described. These strategies include siRNA-mediated silencing of TRPM4, dominant-negative TRPM4 variants, and anti-TRPM4 antibodies. TRPM4 is receiving more and more attention and is likely to be the topic of research in the future.